Dissolved greenhouse gases (nitrous oxide and methane) associated with the naturally iron-fertilized Kerguelen region (KEOPS 2 cruise) in the Southern Ocean (2015)
ABSTRACT: The concentrations of greenhouse gases (GHGs), such as nitrous oxide (N2O) and methane (CH4), were measured in the Kerguelen Plateau region (KPR). The KPR is affected by an annual microalgal bloom caused by natural iron fertilization, and this may stimulate the microbes involved in GHG cycling. This study was carried out during the KEOPS 2 cruise during the austral spring of 2011. Oceanographic variables, including N2O and CH4, were sampled (from the surface to 500 m depth) in two transects along and across the KRP, the north–south (TNS) transect (46◦–51◦ S, ∼ 72◦ E) and the east–west (TEW) transect (66◦–75◦ E, ∼ 48.3◦ S), both associated with the presence of a plateau, polar front (PF) and other mesoscale features. The TEW presented N2O levels ranging from equilibrium (105 %) to slightly supersaturated (120 %) with respect to the atmosphere, whereas CH4 levels fluctuated dramatically, being highly supersaturated (120–970 %) in areas close to the coastal waters of the Kerguelen Islands and in the PF. The TNS showed a more homogenous distribution for both gases, with N2O and CH4 levels ranging from 88 to 171 % and 45 to 666 % saturation, respectively. Surface CH4 peaked at southeastern stations of the KPR (A3 stations), where a phytoplankton bloom was observed. Both gases responded significantly, but in contrasting ways (CH4 accumulation and N2O depletion), to the patchy distribution of chlorophyll a. This seems to be associated to the supply of iron from various sources. Air–sea fluxes for N2O (from −10.5 to 8.65, mean 1.25 ± 4.04 μmol m−2 d −1) and for CH4 (from 0.32 to 38.1, mean 10.01 ± 9.97 μmol−2 d −1) indicated that the KPR is both a sink and a source for N2O, as well as a considerable and variable source of CH4. This appears to be associated with biological factors, as well as the transport of water masses enriched with Fe and CH4 from the coastal area of the Kerguelen Islands. These previously unreported results for the Southern Ocean suggest an intense microbial CH4 production in the study area.